1988
DOI: 10.1016/s0022-5347(17)42131-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Transfected v-Harvey- Ras Oncogene in a Dunning Rat Prostate Adenocarcinoma and the Development of High Metastatic Ability

Abstract: To investigate the role of oncogenes in the development of metastatic ability by prostatic cancer, the viral-Harvey-ras (v-H-ras) oncogene was introduced into the Dunning rat prostate adenocarcinoma cell line, AT2.1 by means of DNA transfection. The AT2.1 cell line is a cloned cell line that is anaplastic, rapidly growing, and has low metastatic potential; after subcutaneous (s.c.) inoculation in syngeneic rats, fewer than 10% of inoculated rats develop distant metastases. Calcium phosphate mediated DNA transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Accordingly, several groups have shown that expression of oncogenes can affect Na + channels [23,24], K ÷ channels [25][26][27][28] and Ca 2+ channels [23,29,30] and that these changes may in turn bring about profound effects on cell behaviour. In particular, the ras family of oncogenes, which can be involved in metastasis [31,32], also plays an important role in nerve growth factor-induced neuronal differentiation and induction of voltage-gated Na + channels [33 35]. Developmental differentiation of human retinoblastoma cells in vitro has also been found to be accompanied by expression ofNa + channels [36].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several groups have shown that expression of oncogenes can affect Na + channels [23,24], K ÷ channels [25][26][27][28] and Ca 2+ channels [23,29,30] and that these changes may in turn bring about profound effects on cell behaviour. In particular, the ras family of oncogenes, which can be involved in metastasis [31,32], also plays an important role in nerve growth factor-induced neuronal differentiation and induction of voltage-gated Na + channels [33 35]. Developmental differentiation of human retinoblastoma cells in vitro has also been found to be accompanied by expression ofNa + channels [36].…”
Section: Discussionmentioning
confidence: 99%
“…Mohler and associates used time-lapse videomicroscopy and a visual grading system to predict successfully the metastatic potential of sublines of the Dunning R-3327 rat prostatic adenocarcinoma model (8-10, 15, 16, 20). In the been produced by v-Harvey-ras transfection (22) that was associated with increased cell motility (19). Increased metastatic potential has also been associated with more negative cell surface change that can be measured electrophoretically (4) or by flow cytometry (5).…”
Section: Discussionmentioning
confidence: 99%
“…This RMC1 cell line was maintained as a monolayer culture in RPMI 1640 medium/10%o fetal bovine serum (HyClone), containing streptomycin (100 ,g/ml), penicillin (100 units/ml), and dexamethasone (250 nM) (standard medium) at 370C in 5% C02/95% air. RMC1 cells were transfected either with plasmid pY3, which encodes the hygromycin B-resistance gene (12), or with plasmid prasZip-6, which encodes the v-Ha-ras oncogene plus the neomycin-resistance gene (13) (i.e., coding for resistance to the G-418 neomycin analog) by the calcium phosphate precipitation procedure as described (14). Five independent clones were obtained from RMC1 cells transfected with plasmid pY3 and nine independent clones were obtained from RMC1 cells transfected with plasmid prasZip-6 using hygromycin B (500 ,&g/ml) selection and G-418 (500 ;Lg/ml) selection, respectively, as described (14).…”
Section: Methodsmentioning
confidence: 99%